Analysis of the factors that influence consumers in purchasing motorcycles in Jakarta Utara - Bayu Wirakusuma (Institute of Accounting Research and Novation (IARN), 2022)
Research's objective is to find factors which affect consumer buying of motorcycles in South Jakarta. In general, researchers have made questions that are based on variables that form the group of factors which finally became factors affecting consumer buying. This research uses the quantitative approach with non-probability sampling technique, convenience type. The amount of respondents is 200; consisting of 64 women and 134 men. Statistics's quantified by SPSS and factor analysis method. Research's results are that there are six factors affecting consumer buying of motorcycles; first is aftersales, second is type, third is reference group, fourth is feature, fifth is design, and sixth is price.